Correlation of glycated haemoglobin status with the foot ulcer - Sachar, Rupali Kaur; Rao, Hemashankar; Sharma, P. P.; Aggarwal, M. P.; Yadav , Sunita (International Surgery Journal, 2023)
Background: Diabetic foot ulcer is a well-documented complication of uncontrolled diabetes and its association with the variables involved in Diabetes like FBS, RBS and HBA1C has been thoroughly researched. This research aims to identify the association of diabetic foot ulcer under Wagner classification with HBA1C classes. Objectives were to determine the severity of diabetic foot ulcer at various level of HBA1C and determine the association. Methods: A observational cross-sectional study with 160 diabetic patients who after giving consent filled questionnaires. The information was analyzed using SPSS v26 (IBM) through Chi Square test. The results were tabulated and inferred from. Results: The study included Sample size of 160 Patients. Here in the study mean age for group A was 41.2 years, for group B it was 29.6 years and for group C it was 25.8 years. Majority 40% patients in group A had T2DM. In group B we found that 51.7% patients had T2DM followed by 48.2% patients with T1DM. In group C we found that majority 67.01% patients had T2DM. We found that site of ulcer was improving with increasing duration of follow up. Initially we found 30% patients with infection at dorsum aspect of foot. After follow up day 9 we found improvement in ulcer infection Conclusions: This research further supplemented an already strongly established association between uncontrolled diabetes and diabetic foot ulcer. We focused on specifically HBA1C and how increased lab values are linked with different grades of Diabetic Foot ulcer and found a strong association demanding a proactive approach towards patient care and education. HbA1c has a linear relationship with the grades of Wagner classification of diabetic foot.